Born Entrepreneurs, Born Leaders : How Your Genes Affect Your Work Life. - Shane, Scott (Oxford University Press, USA, 2010)
It's no secret that your genes have a subtle, but powerful impact on your job and career. But did you know that your DNA accounts for one third of the difference between you and your co-workers in many aspects of work life, from job satisfaction to income level? That's the revelation of this fascinating book--one that will change the way you think It's no secret that your genes have a subtle, but powerful impact on your job and career. But did you know that your DNA accounts for one third of the difference between you and your co-workers in many aspects of work life, from job satisfaction to i.